치매 환자의 초조행동 관련변인에 관한 메타분석 - 박희옥(Park, Heeok); 강민숙(Gang, Minsuk); 박은실(Park, Eunsil) (Sŏngin Kanho Hakhoe chi, 2016)
Purpose: The purpose of this study was to provide basic data about agitation in patients with dementia by surveying the literature. Method: Key words used for search through hand-search and electronic database (CINHAL, Pubmed, Google scholar, Riss, Kiss, DBpia) included 'dementia', 'Alzheimer disease', 'agitation', 'aggression or aggressive behavior', 'problem or disruptive behavior', and 'abnormal behavior.' Seventeen studies met the inclusion criteria for the Meta-analysis and 'R' version 3.2.2 was used to analyze the correlated effect size. Results: Study results showed that variables related to agitation were identified as the demographic (age, gender), dementia-related (cognition, medication uses), physical (Activity of Daily Living [ADL], pain), psychological (depression, psychotic symptom, caregiver burden) and environmental (psychosocial environment) factors. The effect size between the correlated variables and agitation were low to moderate (caregiver burden .36; ADL -.24; psychotic symptom and depression .21; pain .19; cognition -.15; medication uses .12; and psychosocial environment -.12). Conclusion: Based on the findings of this study, strategies to improve patients' depressive and psychotic symptoms and ADL and to reduce caregivers' burden are needed for prevention and management of agitation in patients with dementia.